Comparison of glycated hempglobin with HPLC and capillary electrophoresis - Warade, Jayesh (International Journal of Research in Medical Sciences, 2017)
Background: Hemoglobin A1c, also called A1c or glycated hemoglobin, is hemoglobin with glucose attached. The A1c test evaluates the average amount of glucose in the blood over the last 2 to 3 months. The higher the level of glucose in the blood, the more glycated hemoglobin is formed. Once the glucose binds to the hemoglobin, it remains there for the life of the red blood cell – normally about 120 days. The predominant form of glycated hemoglobin is referred to as A1c. Testing of HbA1c levels via capillary electrophoresis is a relatively new but well-validated method that separates A1c and other Hb fractions via charge difference at high voltage using electro-osmotic flow. This method can be useful in patients who possess such variant hemoglobins because it has a longer runtime, leading to better resolution. Methods: We have processed random samples coming to our laboratory for HbA1C analysis on both the analyzers Biorad D 10 (HPLC method) and Sebia Flex piercing (Capillary Electrophoresis). Results: The value of t is 0.056748 for paired ’t’ test. The value of p is 0.954819. The result is not significant at p≤0.05. There is no significant difference between the results obtained from both the equipment. Conclusions: From this study, it is concluded that the results obtained after testing samples in Sebia Flex Piercing II and Biorad D10 are comparable and there is no significant difference in the results obtained. The advantage of of using Sebia is detection of underlying hemoglobinopathies is easier and can serve as passive surveillance in population that will provide additional information for multidisciplinary approach of treatment. Whereas Biorad D10 has benefit of shorter testing time and is cost effective.